Bamboo Technology Improvement in Reinforcement of Embankment - Nazri, Rabiatul Adawiyah; Zainorabidin, Adnan (Recent Trends in Civil Engineering and Built Environment, 2025)
Peat soil known as problematic soil in construction industry and very fibrous due to the presence of a lot of degraded materials and organic matter, which makes it highly compressible, weak at shear strength, and low in bearing capacity. This property renders it unsuitable for use as a foundation or sub-grade since it would have a significant influence on deformation and settling if not properly handled. And lead to occur such as large settlement, failure of pre-and post-construction, and long-term effects in various ways. The objectives of this study are to measure settlement with and without load on the embankment over peat soil. And to investigate performance reinforcement system by using bamboo technology. To overcome this problem, bamboo is recognized as a potential natural reinforcing material for improvement and stabilization of soil. This study was applied three different layers of loads which are each layer consist of 120 kg. Bamboo high rate of biomass production and renewability in sustainably managed bamboo plantations are definitely important features. The behavior of bamboo also helps in increasing its unit weight hence the shear strength and load bearing power. This research project contributes to the advancement of fundamental knowledge in the preparation of reinforcing works on peat soil is compulsory.